Elements of the mythology of the Regained Territories in the works of Halina Auderska and Zygmunt Trziszka = Elementy mitologii tzw. Ziem Odzyskanych w utworach Haliny Auderskiej i Zygmunta Trziszki - Gieba, Kamila (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
Zygmunt Trziszka and Halina Auderska were analyzed. The ways of constructing the mythology of the Regained Territories were pointed out. They include, for example, the use of culture-motifs and topos related to space and travel (e.g. the theme of Odysseus`s journey and expedition to the golden fleece in Trziszka`s prose), as well as the negative reinterpretation of settlement threads (elements of anti-arcadia in Auderska`s novels). Based on the analysis of literary material, the character of narrative about the Recovered Territories was pointed out - its political, foundation, mythological and psychological aspects.
Keywords: Ziemie Odzyskane; literatura osadnicza; mitologia; migracja; tradycja literacka; Regained Territories; migration; Polish literature; mythology; literary tradition